Catalytic aquathermolysis upgrading of heavy oil with MoS2 oil-in-dispersion emulsion - Yuchen Zhong; Jinghuan Liu; Jun Nan; Hongzuo Zhao; Xinfeng Ju; Xiongfei Li; Dong Wang; Binfei Li; Yongming Chai; Xufeng Lin; Jiqian Wang (Fuel, 2027)

Deformation and global buckling analysis of long-distance shallowly embedded subsea pipeline under strike-slip fault displacement - Zhenmian Li; Xinfeng Pang; Zhengle Xiang; Haoxi Zhang; Zeheng Li; Changxi Wang; Jiacheng Lin (Ocean Engineering, 2026)

Observational evidence of stronger subsidence and more active photochemistry aloft associated with severe ozone pollution over rural areas - Zhuang Wang; Yujia Chen; Hao Zhang; Xianguang Ji; Xiaoyun Sun; Meng Zhang; Xinfeng Lin; Shaowei Yan; Congzi Xia; Kaidi Zhang; Xintong Chen; Yizhi Zhu; et al. (Atmospheric Research, 2026)

Integrating DNA tetrahedron with affinity magnetic levitation for selective capture and sensitive detection of circulating tumor cells - Zilong Zhang; Sidi Cun; Yuxuan Yuan; Yujin Lin; Yitao Cao; Yinzi Chen; Jing Zhang; Jing Wang; Xinfeng Zhao (Analytica Chimica Acta, 2026)

Enhancement of gel properties of soy protein isolate by Polygonatum odoratum polysaccharide: Insight into aggregation, conformation, and interaction - Zheng Qian; Yi Dong; Kening Jin; Zhouyi Mao; Yuncheng Wu; Zhenwen Lin; Xinfeng Zhang; Sijie Zhang (Food Research International, 2026)

Effects of Three Microbiome-Based Therapies on Loperamide-Induced Constipation in Mice by Restoring Intestinal Motility and Modulating the Intestinal Microbiota - Xinfeng Bai; Lin Xu; Kai Wang; Lei Chen; Tianyu Bai; Peipei Li; Weihua Chu; Chao Song (Probiotics and Antimicrobial Proteins, 2026)

Bacillus and lactic acid bacteria inoculation to transform kitchen waste using Hermetia illucens - Guoyou Deng; Min Yan; Shengzhi Yang; Lin Ji; Xinfeng Han; Xiumei Yu; Ke Zhao; Likou Zou (Journal of Environmental Sciences, 2026)

Self-reporting and high-energy supercapacitors enabled by electrochromic ZnCo-S@CuFe-LDH heterostructures via interfacial engineering - Jiale Hou; Zhenghu Zhu; Haofeng Lu; Hecong Wang; Cheng Chen; Xinfeng Wu; Yonghou Xiao; Wanghui Wei; Minjie Xue; Lexing You; Xinzhou Ma; Donghai Lin (Chemical Engineering Journal, 2026)

Engineered albumin host for ratiometric fluorescent indicator-displacement assay: Distinguishing testosterone from estrone and estradiol - Yuting Luo; Linhui Peng; Zhang Lin; Zhiqing Xun; Na Li; Naiyu Liu; Yalong Wang; Xinfeng Du; Tianyi Qin; Bin Liu; Mingqiang Zhu (Chemical Engineering Journal, 2025)

Synergistic band structure tailoring and texturing enhance cooling-power generation Bifunctionality in Bi0.4Sb1.6Te3 - Lin Liao; Jingjing Cui; Keke Liu; Xili Wen; Xingyan Dong; Ming Liu; Ding Luo; Yu-Ke Zhu; Xianli Su; Jiehe Sui; Jinsong Wu; Xinfeng Tang (Chemical Engineering Journal, 2025)

Real-traffic emissions of CO, NOx, CO2, and PM2.5 from vehicles using a portable emission measurement system - Chunying Lu; Shuwei Dong; Shanqian Huang; Shuohan Gao; Jinsheng Fu; Xinyi Tian; Sha Lin; Xinzhu Xiong; Xinjun Wang; Xinfeng Wang (Air Quality, Atmosphere & Health, 2025)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Effects of filter-feeding fish faeces on microbial driving mechanism of lake sediment carbon transformation - Yiming Li; Xuan Che; Hongyuan Chen; Zhanpeng Meng; Xinfeng Li; Xiaodong Wang; Lin Zhu; Yunlong Zhao (Science of The Total Environment, 2024)

Integrating fecal pollution markers and fluorescence analysis for water quality assessment of urban river - Zejun Liu; Jinlong Yuan; Yingying Lin; Feng Lin; Bingjun Liu; Qidong Yin; Kai He; Xinfeng Zhao; Haoxian Lu (Science of The Total Environment, 2024)

Direct measurement of brake and tire wear particles based on real-world driving conditions - Qijun Zhang; Tiange Fang; Zhengyu Men; Ning Wei; Jianfei Peng; Tianqiang Du; Xinfeng Zhang; Yao Ma; Lin Wu; Hongjun Mao (Science of The Total Environment, 2024)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

PanGu Drug Model: learn a molecule like a human - Xinyuan Lin; Chi Xu; Zhaoping Xiong; Xinfeng Zhang; Ningxi Ni; Bolin Ni; Jianlong Chang; Ruiqing Pan; Zidong Wang; Fan Yu; Qi Tian; Hualiang Jiang; et al. (Science China Life Sciences, 2023)

Impact of miR-200b and miR-495 variants on the risk of large-artery atherosclerosis stroke - Shanmei Qin; Chong Shen; Wuzhuang Tang; Mengmeng Wang; Ying Lin; Zhaojun Wang; Yunzi Li; Zhizhong Zhang; Xinfeng Liu (Metabolic Brain Disease, 2023)

Conserved and divergent evolution of the bZIP transcription factor in five diploid Gossypium species - Fangting Ye; Xiaogang Zhu; Shaofang Wu; Yunyue Du; Xinfeng Pan; Yuchen Wu; Zhengyi Qian; Zhaowei Li; Wenxiong Lin; Kai Fan (Planta, 2023)

Impact of Petroleum Contamination on the Structure of Saline Soil Bacterial Communities - Ying Zhang; Xiaojie Sun; Cheng Qian; Lin Li; Xiufang Shang; Xinfeng Xiao; Yu Gao (Current Microbiology, 2022)

Amniotic fluid mesenchymal stem cells repair mouse corneal cold injury by promoting mRNA N4-acetylcytidine modification and ETV4/JUN/CCND2 signal axis activation - Xinfeng Fei; Yuying Cai; Feng Lin; Yongyi Huang; Te Liu; Yan Liu (Human Cell, 2021)
Severe corneal injury is one of the main causes of loss of visual function. Mesenchymal stem cells (MSCs) have the ability to repair damaged cells in vivo. The present study aimed to explore whether MSCs could function as a cell therapy tool to replace traditional methods to treat corneal injury. CD44 + /CD105 + mesenchymal stem cells isolated from mouse amniotic fluid (mAF-MSCs) were injected into mice after cryoinjury to induce corneal endothelial cell injury. Histopathological assays indicated that mAF-MSCs could promote the growth of corneal epithelial cells, reduce keratitis, and repair the corneal damage caused by low temperature. cDNA microarray analysis revealed that the mAF-MSCs affected the expression patterns of mRNAs related to cell proliferation and differentiation pathways in the mice after transplantation. The results of quantitative real-time PCR and western blotting revealed that NAT12, NAT10, and the ETV4/JUN/CCND2 signaling axis were elevated significantly in the mAF-MSC-transplantation group, compared with those in the phosphate-buffered saline-treated groups. High performance liquid chromatography–mass spectroscopy results revealed that mAF-MSCs could promote mRNA N4-acetylcytidine (ac4C) modification and high expression of N -acetyltransferase in the eyeballs. RNA immunoprecipitation-PCR results showed that a specific product comprising Vegfa , Klf4 , Ccnd2 , Jun , and Etv4 mRNA specific coding region sites could be amplified using PCR from complexes formed in mAF-MSC-transplanted samples cross-linked with anti-ac4C antibodies. Thus, mouse amniotic fluid MSCs could repair the mouse corneal cold injury by promoting the ETV4/JUN/CCND2 signal axis activation and improving its stability by stimulating N4-acetylcytidine modification of their mRNAs.

HDAC9 Polymorphisms Predict Susceptibility, Severity, and Short-Term Outcome of Large Artery Atherosclerotic Stroke in Chinese Population - Mengmeng Wang; Mengmeng Gu; Zibao Li; Bo Sun; Xi Cheng; Zhengze Dai; Shun Li; Lulu Xiao; Min Zhao; Zhaojun Wang; Ying Lin; Yahong Liu; et al. (Journal of Molecular Neuroscience, 2019)

Mapping of Id locus for dermal shank melanin in a Chinese indigenous chicken breed - Jiguo Xu; Shudai Lin; Xinfeng Gao; Qinghua Nie; Qingbin Luo; Xiquan Zhang (Journal of Genetics, 2017)

Dissipation of phenanthrene and pyrene at the aerobic–anaerobic soil interface: differentiation induced by the rhizosphere of PAH-tolerant and PAH-sensitive rice (Oryza sativa L.) cultivars - Yan He; Wen Xia; Xinfeng Li; Jiajiang Lin; Jianjun Wu; Jianming Xu (Environmental Science and Pollution Research, 2015)